Identification and quantitative analysis of rice aroma compounds in black jasmine and Sung-yod Korat rice from Nakhon-Ratchasima province, Thailand / Vanida Choomuenwai - Choomuenwai, Vanida (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
Black jasmine and Sung-yod Korat rice were two new types of rice promoted to cultivar in Nakhon Ratchasima province, Thailand. This research aimed to identify and quantitatively compare rice aroma compounds in black jasmine rice with aromatic compounds in Sung-yod Korat rice. Headspace was used to collect and concentrate the compounds in rice. The rice was preheated in headspace, and subsequent GC-MS analysis was performed. The identification was confirmed by comparing both mass spectra and retention values of 2-Acetyl-1-pyrroline (2AP) standards and samples. 2AP was reported as the key aromatic compound for aromatic rice. The results showed that the concentration of 2AP in black jasmine rice and Sung-yod Korat rice were 0.77± 0.03, and 0.52± 0.01 ppm, respectively.